2021
DOI: 10.1016/j.jid.2020.09.010
|View full text |Cite
|
Sign up to set email alerts
|

iRHOM2: A Regulator of Palmoplantar Biology, Inflammation, and Viral Susceptibility

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Since the role of Rhomboid proteins was first demonstrated in the Drosophila EGF signaling pathway [ 46 , 53 ], the most characterized function of Rhomboid proteases conserved through organisms, including bacteria, animals and plants, is the proteolytic cleavage of membrane proteins [ 30 , 31 , 54 ]. Later, this family of proteins was implicated in diverse cellular processes, including protein homeostasis, viral susceptibility, mitochondria membrane fusion and parasite–host interaction [ 34 , 39 , 40 , 55 , 56 , 57 , 58 , 59 , 60 ]. The genetic and biochemical data presented in this study suggest that KOM acts not as a Rhomboid protease but as a member of the growing sub-family of proteolytically inactive Rhomboid-like proteins ( Supplementary Figure S3 ) [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the role of Rhomboid proteins was first demonstrated in the Drosophila EGF signaling pathway [ 46 , 53 ], the most characterized function of Rhomboid proteases conserved through organisms, including bacteria, animals and plants, is the proteolytic cleavage of membrane proteins [ 30 , 31 , 54 ]. Later, this family of proteins was implicated in diverse cellular processes, including protein homeostasis, viral susceptibility, mitochondria membrane fusion and parasite–host interaction [ 34 , 39 , 40 , 55 , 56 , 57 , 58 , 59 , 60 ]. The genetic and biochemical data presented in this study suggest that KOM acts not as a Rhomboid protease but as a member of the growing sub-family of proteolytically inactive Rhomboid-like proteins ( Supplementary Figure S3 ) [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A proteolytically inactive rhomboid protein (iRhom2) encoded by Rhbdf2 gene involved in innate immunity against viral infections [ 165 ], regulates trafficking of pro-ADAM17 from endoplasmic reticulum to Golgi apparatus where furin detaches ADAM17 inhibitory prodomain to make it mature, substrate specific and be prepared for expression on the cell surface in complex with iRhom2 [ 166 , 167 ]. Infection with DNA and RNA viruses (influenza A, RSV) upregulates Rhbdf2 and ADAM17 genes [ 167 ]. However, an in vivo study revealed that ADAM17-dependent ectodomain shedding is a saturable phenomenon: it does not increase significantly when ADAM17 expression rises above a certain level [ 168 ].…”
Section: Adam17 the Sheddase Of Ace2mentioning
confidence: 99%
“…List of used experiment IDs for indicated tissue and primary cells: a) murine heart: MM-00170 (Muchir et al, 2007), MM-00253 (Dufour et al, 2007), MM-00257 (Zhao et al, 2007), MM-00262 (Alcendor et al, 2007), MM-00300 (Ramchandran et al, 2006), MM-00322, (Thorrez et al, 2008), MM-00330 (Lattin et al, 2008), MM-00368 (Barger et al, 2008), MM-00384 (Wong et al, 2010), MM-00476 (Abd Alla et al, 2016), MM-00485 (Oka et al, 2011), MM-00492 (Wang et al, 2016), MM-00497 (Shuai et al, 2011), MM-00507 (Shuai et al, 2011), MM-00561 (Ricard et al, 2010), MM-00834 (Traister et al, 2013), MM-00841 (Mercader et al, 2012), MM-01538 (Gambino et al, 2013), MM-01642 (Lucas et al, 2014), MM-01875 (Lucas et al, 2014); b) murine primary fibroblast (dermis): MM-00159 (Vallender and Lahn, 2006), MM-00180 (Vallender and Lahn, 2006), MM-00627 (Garinis et al, 2009), MM-00724 (Garinis et al, 2009); c) murine primary keratinocytes: MM-01215 (Allende et al, 2013); d) healthy human epidermis tissue (biopsy): HS-02924 (Esaki et al, 2015); e) human primary keratinocytes (untreated): HS-02625 (Yunoki et al, 2018), HS-02787 (Busch et al, 2008), HS-02490 (Swindell et al, 2012), HS-00220 (Sa et al, 2007); f) human primary keratinocytes (treated with TNFα, IFNα, IFNγ or IL4; 24 h): HS-02490 (Swindell et al, 2012); g) human primary keratinocytes (treated with 10 ng/ml I IFNγ; 96 h): HS-02625 (Yunoki et al, 2018); h) human primary fibroblasts (untreated): HS-00393, HS-00481 (Chen et al, 2008), HS-00805 ...…”
Section: In Silico Gene Expression Analysismentioning
confidence: 99%
“…The genetic disorder causing TOC is caused by single point mutations in the N-terminus (Howel-Evans et al, 1958, Ellis et al, 1994, Blaydon et al, 2012, Saarinen et al, 2012, Ellis et al, 2015, Mokoena et al, 2018). This disorder is characterised by symptoms such as leukoplakia and hyperkeratosis and increases the risk of OSCC (Chao-Chu et al, 2021). The mutations are classified as “gain of function” because they apparently upregulate ADAM17 activity, resulting in higher levels of EGFR ligands, EGFR hyperactivation in keratinocytes and increased release of TNF receptor 1, leading to reduced apoptosis (Blaydon et al, 2012, Maney et al, 2015, Hosur et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%